Islamic Ethics and Morality in the Educational Bureaucracy: Theoretical and Practical Review - Firmansyah, Firmansyah; Husni, Miftahul; Rosad, Ade; Al Ghozali, Muhammad Iqbal; Kaca, Gatot (INCARE, International Journal of Educational Resources, 2025)
This research aims to analyze the concept of ethics and morality in Islam that can be applied in the education bureaucracy, identify the challenges faced in the application of Islamic ethics and morality in the education bureaucracy, and offer strategies for implementing Islamic values to create a more transparent, fair, and quality-oriented system. This research uses a library research method with a narrative review approach. Data were obtained through literature analysis from various relevant academic sources in the last 10 years. The analysis technique used is thematic analysis to identify patterns and main themes related to Islamic ethics and morality in the education bureaucracy. The results show that the application of Islamic values, such as honesty (shidq), trustworthiness, justice and ihsan, can improve effectiveness and transparency in the education bureaucracy. However, its implementation faces various challenges, including corruption, lack of transparency, low ethical awareness among education bureaucrats, and weak Islamic values-based regulations. To overcome these obstacles, strategies that can be implemented include Islamic ethics education and training for bureaucrats, strengthening regulations, improving technology-based monitoring systems, and exemplary leadership in the education bureaucracy. The implications of this research show that an education bureaucracy based on Islamic ethics and morality can create an education system that is more integrity, professional, and oriented towards the welfare of the community. Therefore, this research recommends further studies on the application of technology in the supervision of the education bureaucracy as well as more effective policy models in instilling Islamic values in the education administration system.